Long term effect of INM on aonla (Emblica officinalis) and soil quality under rainfed hot semi-arid environment - SINGH, A K; SINGH, SANJAY; APPA RAO, V V; HIWALE, S S; JOSHI, H K (The Indian Journal of Agricultural Sciences, 2014)
The experiment was conducted on seven and eight years old aonla (Emblica officinalis Gaertn) tree of NA-7 to study the influence of various levels of organic (FYM and biofertilizers) and inorganic (NPK) sources of nutrients on morphometrix, productivity and quality attributes of aonla and soil quality during 2009-10 and 2010-11 under hot semi-arid ecosystem. Significant improvement was recorded in soil quality by application of different combinations of NPK, FYM and biofertilizers. The vegetative growth, yield and quality of aonla were influenced significantly by different sources of nutrients. The maximum vegetative growth was recorded in the plants which were applied with standard doses of NPK which was followed by farmyard manure plus 50% of the standard dose of NPK. The maximum mean yield per plant (48.45 kg) was recorded in the plants treated with standard doses of NPK followed by FYM + 50% of standard dose of NPK (45.27 kg). TSS, total sugar, vitamin C and total phenols were influenced considerably by the application of different organic sources of nutrients being highest in T5 (FYM + Azotobactor + VAM) treatment. The soil properties in terms of pH and EC declined whereas hydraulic conductivity, organic carbon increased from their initial values with the application of various organic sources of nutrient in different combinations, while pH, EC, hydraulic conductivity, bulk density and organic carbon of the basin soil treated with standard dose of NPK were not improved considerably.